Yarning with a remote Aboriginal community about the next steps for achieving healthy skin - Rebecca Dalton; Erin Victor; Hannah M.M. Thomas; Stephanie L. Enkel; Bep Uink; Rebecca Bennett; Slade Sibosado; Asha C. Bowen (Australian and New Zealand Journal of Public Health)
Objective: Skin health is widely recognised as being important for overall good health and well-being, yet the burden of skin infections in remote Aboriginal communities remains high. This project aimed to explore if virtual support for skin health could be a strategy to reduce community barriers to skin health engagement. Methods: This study collected qualitative data using a yarning methodology within a participatory action research design. A community co-researcher who was intimately familiar with the Country, language, and community in which this study was based was employed to guide the research process. Results: The final dataset comprised of interviews with 21 participants. Three primary themes were identified including: Reach Further into the Community with Education and Skin Checks, Virtual Skin Health Support is not Preferred but Acceptable, and Environmental Health Cannot be Ignored. Conclusions: Participants provided several suggestions on improving health promotion messaging within community whilst emphasising the need for a stronger focus on environmental health. The employment of a community co-researcher was integral to informing the methodology. Implications for Public Health: This project provides further evidence of the significance of community engagement, inclusion and capacity building when conducting research in remote Aboriginal communities and the benefits of two-way learning as foundational to good research practices.